2020
DOI: 10.1111/febs.15506
|View full text |Cite
|
Sign up to set email alerts
|

A guide to measuring phagosomal dynamics

Abstract: Phagocytosis is an essential mechanism for immunity and homeostasis, performed by a subset of cells known as phagocytes. Upon target engulfment, de novo formation of specialized compartments termed phagosomes takes place. Phagosomes then undergo a series of fusion and fission events as they interact with the endolysosomal system and other organelles, in a dynamic process known as phagosome maturation. Because phagocytes play a key role in tissue patrolling and immune surveillance, phagosome maturation is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 198 publications
1
5
0
Order By: Relevance
“…Our research began with validating and measuring the effective labeling of CLIO-AF647 nanoparticles by macrophages in vitro. In accordance with previous studies, 30 we found that CLIO-AF647 nanoparticles fuse with lysosomes when internalized by macrophages. We further optimized the detection capabilities of the MRI and fluorescence imaging modalities.…”
Section: Discussionsupporting
confidence: 93%
“…Our research began with validating and measuring the effective labeling of CLIO-AF647 nanoparticles by macrophages in vitro. In accordance with previous studies, 30 we found that CLIO-AF647 nanoparticles fuse with lysosomes when internalized by macrophages. We further optimized the detection capabilities of the MRI and fluorescence imaging modalities.…”
Section: Discussionsupporting
confidence: 93%
“…2 A and S2 A). To improve the uptake efficiency, the particles were opsonized with rabbit immunoglobulin (Ig) G raised against streptavidin, which facilitates Fc-receptor-mediated uptake by human macrophages and DCs ( 15 ) ( Figs. 2 A and S2 A).…”
Section: Resultsmentioning
confidence: 99%
“…The disappearance of Myc-VAMP5 from the phagosome could be due to pinching off by tubulation/scission or vesiculation and (or) internalization within the phagosome by inward budding via intraluminal vesicle for degradation ( Fairn and Grinstein, 2012 ; Lancaster et al. , 2021 ; Levin-Konigsberg and Mantegazza, 2021 ). Our microscopic analysis failed to detect any Myc-VAMP5 signal within phagosomes where the surface Myc-VAMP5 signal had already disappeared ( Figure 4B ; Supplemental Figure S6).…”
Section: Discussionmentioning
confidence: 99%